2019
DOI: 10.1177/0734904119839917
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on combustion characteristics of blended fuel pool fires

Abstract: Liquid–vapor phase equilibrium theories are used to analyze boiling processes of blended fuel pool fires, and the results show that there are two boiling mechanisms (azeotropism and non-azeotropism) for blended fuels compared with single-component fuels. A series of pool fire experiments were conducted to investigate the combustion characteristics of blended fuel pool fires. The experimental results showed that the two boiling mechanisms have different effects on the burning process of the fuel blends. The boi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Various grid quantities are chosen to simulate the temperature value at a height of 0.3m for grid independence analysis, as shown in Figure 3-4. Comparison with actual experimental data under similar conditions [6] It can be observed that with an increasing number of grids, the simulated temperature values stabilize. The simulated data closely matches the experimental data when the grid quantity reaches 108000.…”
Section: Grid Independence Analysis and Model Verificationmentioning
confidence: 88%
“…Various grid quantities are chosen to simulate the temperature value at a height of 0.3m for grid independence analysis, as shown in Figure 3-4. Comparison with actual experimental data under similar conditions [6] It can be observed that with an increasing number of grids, the simulated temperature values stabilize. The simulated data closely matches the experimental data when the grid quantity reaches 108000.…”
Section: Grid Independence Analysis and Model Verificationmentioning
confidence: 88%